The Role of Semaphorin 4D in Bone Remodeling and Cancer Metastasis - Lontos, Konstantinos; Adamik, Juraj; Tsagianni, Anastasia; Galson, Deborah L.; Chirgwin, John M.; Suvannasankha, Attaya (Frontiers in Endocrinology, 2018)
Semaphorin 4D (Sema4D; CD100) is a transmembrane homodimer 150-kDa glycoprotein first discovered in T lymphocytes. It belongs to the family of semaphorins, a group of proteins with significant roles in human physiology. They were first identified as chemorepellants that cause growth cone collapse and guide the neural axons to the desired junction. The current literature reveals many additional roles for Sema4D, including activation of platelets, angiogenesis, potentiation of cancer cells, regulation of bone formation and modulation of the immune response. This review focuses on the role of Sema4D in bone and cancer biology and the molecular pathways involved. Recent studies suggest Sema4D may act as a coupling factor, secreted by osteoclasts to inhibit osteoblasts. Therefore, Sema4D blockade may have bone-anabolic potential. Sema4D and its receptor Plexin-B1 are overexpressed in many cancers and associated with invasive phenotypes, skeletal metastasis, angiogenesis and immune escape. Therefore, this review explores the emerging field of the interaction of cancer cells with the bone through the Sema4D-Plexin-B1 pathway, which is extremely pertinent in the light of the first humanized Sema4D neutralizing antibody now undergoing early phase clinical trials.